Urgensi Perluasan Kewenangan MK Terhadap Constitutional Question dan Constitutional Complaint Sebagai Wujud Perlindungan Hak Konstitusional Warga Negara - Supriardoyo Simanjutak; Ridho Alfaiz; Melisa Ambarita (Jurnal Legislatif, 2021)
Abstract The birth of the Constitutional Court as a demand to uphold the norms contained in the Constitution which aims to provide protection of the constitutional rights of citizens who are more democratic, transparent, and just. However, the Constitutional Question and Constitutional Complaint authority that is not owned by the Constitutional Court has caused anxiety to justice seekers. The legal issues studied are how to understand and apply the Constitutional Question and Constitutional Complaint in Other Countries and how the Urgency of Application and Expansion of the Authority of the Constitutional Court in Examining the Constitutional Question and Constitutional Complaints. This study uses a normative juridical method accompanied by a comparative study. Based on the results of the study, it can be concluded that the Expansion and Application of Constitutional Questions and Constitutional Complaints in Indonesia is an urgent basic need to be realized as a progressive and responsive legal development. So it is necessary to expand and implement the Constitutional Complaint and Constitutional Question so that it must be formulated in the Duties of Authority of the Constitutional Court Article 24 C paragraph (1) of the 1945 Constitution of the Republic of Indonesia and the Constitutional Court Law. Keywords: Constitutional Question; Constitutional Complaint; Urgency. Abstrak Lahirnya Mahkamah Konstitusi yang selanjutnya disebut MK sebagai tuntutan untuk menegakkan norma-norma yang ada dalam konstitusi yang bertujuan untuk memberikan perlindungan hak-hak konstitusional warga negara yang lebih demokratis, transparan, dan berkeadilan. Namun kewenangan Constitutional Question dan Constitutional Complaint yang tidak dimiliki oleh MK telah menimbulkan keresahan terhadap pencari keadilan. Isu hukum yang dikaji mengenai bagaimana pengertian dan penerapan Constitutional Question dan Constitutional Complaint di negara lain dan bagaimana urgensi penerapan dan perluasan kewenangan MK dalam menguji Constitutional Question dan Constitutional Complaint. Penelitian ini menggunakan metode yuridis normatif disertai dengan kajian perbandingan. Berdasarkan hasil kajian dapat disimpulkan bahwa perluasan dan penerapan Constitutional Question dan Constitutional Complaint di Indonesia merupakan suatu kebutuhan mendasar yang mendesak untuk direalisasikan sebagai pengembangan hukum yang progresif dan responsif. Sehingga perlu dilakukan perluasan dan penerapan Constitutional Complaint dan Constitutional Question sehingga harus dirumuskan dalam tugas kewenangan MK Pasal 24 C ayat (1) UUD NRI Tahun 1945 dan Undang-Undang Mahkamah Konstitusi Kata Kunci : Constitutional Question; Constitutional Complaint; Urgensi.